EARLY OPERATIVE MANAGEMENT OF COMPLICATED APPENDICITIS IS ASSOCIATED WITH IMPROVED SURGICAL OUTCOMES IN ADULTS: A COMPREHENSIVE SYSTEMATIC REVIEW - Gajah, Supriyadi; Martupa Lumbantoruan, Johannes (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: The management of appendicitis has been surgical over the years with high significant efficacy and low complication rate, and is recommended for the treatment of appendicitis in those cases in which there is a dilatation of more than 13 mm of the appendix, mass effect or presence of appendicolith in imaging. However, recent evidence from different series has proposed medical management for this condition in specific high surgical risk populations. The aim: The aim of this study to show about early operative management of complicated appendicitis is associated with improved surgical outcomes in adults. Methods: By the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. This search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed, SagePub, and Google Scholar were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search get 23 articles, whereas the results of our search on SagePub get 151 articles, on Google Scholar 2840 articles. Records remove before screening are 2110, so we get 904 articles fos screening. After we screened based on record exclude, we compiled a total of 10 papers. We included five research that met the criteria. Conclusion: Laparoscopic appendicectomy is becoming the gold standard for the treatment of appendicitis. However, the advantages of the innovations in minimally invasive and endoscopic surgery are unlikely to render formal open appendicectomy obsolete. Nonoperative management with antibiotics may suffice in selected cases with uncomplicated appendicitis.